GENRE-BASED APPROACH IN TEACHING WRITING NARRATIVE TEXT : A Case Study Research at One Public Junior High School in Bandung - Prakoso, Gita Hilmi (2013)
The Genre Based Approach (GBA) is one of the approaches that can be implemented in teaching writing. This study examines the implementation of the Genre Based Approach to Narrative text in one class of grade nine in one public junior high school in Bandung. The study aims to find out whether GBA can help students in developing their writing ability. The study uses a case study research design involving 30 students. Data were obtained from classroom observations for four weeks, in which the researcher acted as a teacher, collection of students' texts over the teaching program, and interviews with three students representing low, middle, and high achiever as recommended by the classroom teacher. The data from observation were analyzed using thematic analysis relevant to the research questions and the theme of Genre-Based Approach. The students' texts were analyzed by using Systemic Functional Grammar (SFG). There were six students' texts chosen to be analyzed. Finally, the interview data were analyzed in steps including transcribing, categorizing, and interpreting the data relating them to the theory. The findings reveal that the implementation of GBA in teaching narrative writing made a good contribution to development of the students' writing ability. The students' narrative texts improved in terms of schematic structures and linguistic features with the teacher's corrective feedback in all stages of teaching. Moreover, students give a positive response to the teaching program, since they found the benefits of the program to allow them to learn explicitly. It is recommended that teaching program be socialized and implemented in other contexts. Key words: Genre-Based Approach, Narrative text